The impact of the service quality on customer loyalty in the algerian banking sector – Acase study at AL-SALAM BANK ALGERIA- - MORKANE Mohamed El Bachir,; BANI Fathi,; SAHOUANE Ali, (Journal of North African Economies, 2025)
This study aims to identify the dimensions of the prevailing service quality. As well to identify the extent of the impact of service quality in customer loyalty in Al-salam bank Algeria. In order to achieve the target, the random sample method was adopted and (120) questionnaires were distributed, (111) have been retrieved and found usable data for analysis, using SPSS. The study proved that there is an impact having statistical significance of the dimensions of service quality (as independent variables) on customer loyalty, these impacts were for the most part weak. Results also showed after using the multiple regression testing that service quality dimensions combined have a significant impact on customer loyalty. The study reached that the SERVQUAL model remains an effective way of measuring customer loyalty. Because customer value is regarded as an asset to banks.